The Prevalence and Impact of Overlapping Rome IV‐Diagnosed Functional Gastrointestinal Disorders on Somatization, Quality of Life, and Healthcare Utilization: A Cross‐Sectional General Population Study in Three Countries. (January 2018) - Aziz, Imran; Palsson, Olafur S; Törnblom, Hans; Sperber, Ami D; Whitehead, William E; Simrén, Magnus
Abstract : OBJECTIVES: The population prevalence of Rome IV‐diagnosed functional gastrointestinal disorders (FGIDs) and their cumulative effect on health impairment is unknown. METHODS: An internet‐based cross‐sectional health survey was completed by 5, 931 of 6, 300 general population adults from three English‐speaking countries (2100 each from USA, Canada, and UK). Quota‐based sampling was used to generate demographically balanced and population representative samples with regards to age, sex, and education level. The survey enquired for demographics, medication, surgical history, somatization, quality of life (QOL), doctor‐diagnosed organic GI disease, and criteria for the Rome IV FGIDs. Comparisons were made between those with Rome IV‐diagnosed FGIDs against non‐GI (healthy) and organic GI disease controls. RESULTS: The number of subjects having symptoms compatible with a FGID was 2, 083 (35%) compared with 3, 421 (57.7%) non‐GI and 427 (7.2%) organic GI disease controls. The most frequently met diagnostic criteria for FGIDs was bowel disorders ( n =1, 665, 28.1%), followed by gastroduodenal ( n =627, 10.6%), anorectal ( n =440, 7.4%), esophageal ( n =414, 7%), and gallbladder disorders ( n =10, 0.2%). On average, the 2, 083 individuals who met FGID criteria qualified for 1.5 FGID diagnoses, and 742 of them (36%) qualified for FGID diagnoses in more than one anatomic region. The presence of FGIDs in multiple regions was associated with increasing somatization, worse mental/physical QOL, more medical therapies, and a higher prevalence of abdominal surgeries; all P <0.001. Notably, individuals with FGIDs in multiple regions had greater somatization and worse QOL than organic GI disease controls. CONCLUSIONS: Roughly a third of the general adult population fulfils diagnostic criteria for a Rome IV FGID. In a third of this subset multiple GI regions are involved and this overlap is associated with increased health impairment.